Bahasa Kasar dan Hierarki Sosial: Kajian terhadap Harga Diri dalam Cerpen-Cerpen Shawal Rajab (LITPAM, 2024)
This study examines the relationship between the use of harsh language and social hierarchy in four short stories by Shawal Rajab (2005), focusing on how language reflects characters’ self esteem based on their social status, education and economic position. Using a qualitative textual analysis, the stories Harga Kemanusiaan, IQ, Batin Terseksa! Oh… Lusa Periksa and Tuntutan are analyzed to understand characters’ communication pattersn and social interactions. The findings indicate that characters with higher social and economic status tend to use harsh, demeaning language to maintain their position, while lower status characters often become targets of disparagement. This study concludes that language serves not only as a communication tool but also as a manifestation of power and self esteem in society, highlighting the relationship between language, power and self-esteem in social interactions.